The Effect of Adding Humic on Some morphological and Productive Properties of Soybeans under Salt Stress Conditions: - Al-Taha, Ghada Mohammed Rashid; Omar, Abdul-mhsin Al-Sayed; Khader, Khaled Ramadan (Journal of agricultural, environmental and veterinary sciences, 2022)
This research was carried out at the Research Center of the University of Aleppo in the Kaskeis area during the two agricultural seasons 2019-2020. The aim of the experiment was to study the effect of irrigation with water of different levels of salinity (1.2, 4.2, 6.5 ds.m-1) and three concentrations of humic organic fertilizer (0, 0.5, 1 g.l-1) and their interaction in some productive and biochemical traits of three soybean cultivars (SB44, SB239, SB314). The experiment was designed in a split plot design with three replications.The results showed that the increase in salinity concentrations of irrigation water from (6.5-1.2 ds.m-1) caused a significant decrease in the production and morphological characteristics. The results also showed significant differences for the interaction between the level of salinity of irrigation water and the addition of humic organic fertilizer In the productive and morphological traits, the highest rate of these studied traits was achieved when overlapping irrigation with the control treatment (1.2 ds.m-1) with the addition of humic organic fertilizer at a concentration of (1 g.l-1) for all studied varieties. The irrigation treatment (6.5 ds.m-1) gave the lowest rate for these characteristics. The humic organic fertilizer had a clear effect in reducing the negative impact of irrigation water salinity in both seasons.
Keywords: salt stress; soybean; Humic acid; Irrigation